Abdominal Surgery With Bilateral Rectus Sheath Block: A Case Report. Issue 7 (1st October 2019) - Duggan, Elizabeth W.; Vadlamudi, Ratna; Spektor, Boris; Sharifpour, Milad
Abstract : A 44-year-old man, American Society of Anesthesiologists physical status class IV, presented for fulguration of anal condyloma and diverting colostomy. The patient's medical history includes World Health Organization (WHO) class I pulmonary hypertension (PH), right heart failure, and bilateral lower extremity paralysis due to Pott's disease. The patient was not a candidate for neuraxial anesthesia due to sacral decubitus ulcers, and alternative options to general anesthesia (GA) were considered to avoid the high risk of right ventricular (RV) failure and ensuing complications. The case was successfully performed under sedation with dexmedetomidine infusion and bilateral rectus sheath blocks for surgical anesthesia.